Farming May 2017 19 Site-Specific Nutrient Management for crop management system - Yadav, Taramani; Ram, Hardev; Yadav, M R; Kumar, Rakesh (Indian Farming, 2017)
Site specific nutrient management provides an approach for feeding crops with nutrients as and when needed to have synergy between nutrient demand and supply of different production system. It involves nutrient application on soil test basis, yield goals, factors influencing crop response to nutrient application. It aims to optimize the supply of nutrients over time and space to match the specific requirements of crops. GPS and GIS based mapping helps to increase awareness at the village scale, helping farmers in appropriate management of nutrients. Therefore, SSNM proved to be advantageous over farmer practices in optimizing nutrient feeding to crops and finally to obtain higher yield and net returns.